PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MODEL KOOPERATIF TIPE STUDENT TEAM ACHIEVMENT DEVISIONS DI SD - Amri, Herlina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this study was to describe the improvement of student learning outcomes in social studies learning with the use of cooperative learning model type STAD Devisions Student Team Achievment  in fourth grade elementary school. This research is a classroom action research using qualitative and quantitative approaches. The subjects were the authors as a class teacher and fourth grade students are about 20 people enrolled in the second semester of academic year 2011/2012 in the fourth grade students of SD Negeri 65 Manggopoh utara has increased. From the research cycle I encounter I can know the percentage value is 62.75% cognitive, affective and psychomotor is 63% of 65.5%. While the second meeting in the first cycle can be determined percentage of the cognitive value is 69.25%, the percentage is 68% affective and psychomotor 69%. Second cycle of research analysis meetings I can know the percentage value is 73% cognitive, affective percentage is 73% and psychomotor 74.3%. While in the second cycle II meeting to know the percentage of the cognitive value is 77%, the percentage is 77% affective and psychomotor was 79.3% Kata kunci : hasil belajar siswa; pembelajaran IPS; model STAD.